Dynamic and Connectionist Approaches to Development: Toward a Future of Mutually Beneficial Coevolution - Thomas, M.; McClelland, J.; Richardson, F.; Schapiro, A.; Baughman, Frank (Oxford University Press, 2009)
© 2009 by John P. Spencer, Michael S. C. Thomas, and James L. McClelland. All rights reserved.A tension has existed between connectionism and dynamic systems theory (DST), and this chapter considers why this should be the case. The chapter argues that much of the tension arises from a tenet that the two approaches share: they both rely on the explicit, quantitative instantiation of ideas in mathematical or computational models. The use of such models is responsible for much of the theoretical progress generated by connectionism and DST beyond the theories of good old-fashioned cognitive development (GOFCD). But the use of explicit, quantitative models brings with it a new set of problems. The chapter discusses several consequences of the use of such models and considers three points of apparent disagreement between connectionism and DST.